Pediatric intussusception in Uganda: differences in management and outcomes with high-income countries - Akello, Valin; Kurigamba, Gideon; Semakula, Daniel; Kakembo, Nasser; Ozgediz, Doruk; Sekabira, John (Journal of pediatric surgery, 2020)
In high-income countries the presentation and treatment of intussusception is relatively rapid, and most cases are correctable with radiographically-guided reduction. In low-income countries, many delays affect outcomes and surgical intervention is required. This study characterizes the burden and outcome of pediatric intussusception in Uganda.